Diagnostic test of urine sample, vaginal smear and combination of urine with vaginal smear to identify Neisseria gonorrhoeae with polymerase chain reaction method - Nadeak, Kristina (International Journal of Research in Medical Sciences, 2019)
Background: Gonorrhoea is a disease caused by Neisseria gonorrhoeae that is transmitted through sexual contact. There are several examinations performed on gonorrhoea infection, one of them is Polymerase Chain Reaction (PCR). The objective is to determine the diagnostic test of urine samples, vaginal smear and combination of urine and vaginal smear in identifying Neisseria gonorrhoeae using the PCR method. Methods: This study is a diagnostic test with a cross-sectional design involving 58 female sex workers (FSW). All FSWs are carried out of history and physical examination. Urine sampling, vaginal smear, combination of urine and vaginal smear, and endocervical smear were obtained for identifying Neisseria gonorrhoeae using PCR method, then a diagnostic test analysis of each sample was performed. Results: The diagnostic test of PCR for Neisseria gonorrhoeae from urine samples was found sensitivity 44.4%, specificity 20.0%, positive predictive value (PPV) 83.3%, negative predictive value (NPV) 3.8% and accuracy 42.0%. From vaginal smear, we obtained sensitivity 34.0%, specificity 66.7%, PPV 88.2%, NPV 12.1% and accuracy 38.0%. And from combination of urine and vaginal smear, we obtained sensitivity 51.1%, specificity 20.0%, PPV 85.2%, NPV 4.3% and accuracy 48.0%. Conclusions: From these results the researchers suggested that urine, vaginal and combination of urine and vaginal smear could not be used as an alternative to examine the sensitivity and specificity of Neisseria gonorrhoeae, so the endocervical sample remained the reference sample for examination of nucleic acid amplification tests for Neisseria gonorrhoeae.